Mesenchymal stem cells prevent overwhelming inflammation and reduce infection severity via recruiting CXCR3+ regulatory T cells. Issue 10 (30th September 2020) - Li, Wenchao; Chen, Weiwei; Huang, Saisai; Yao, Genhong; Tang, Xiaojun; Sun, Lingyun
Abstract: Objectives: Mesenchymal stem cells (MSCs) have shown great potential in treating autoimmune diseases (ADs). Unlike the traditional immunosuppressants, which inadvertently impair patients' antimicrobial immunity, MSCs reduce the incidence and duration of respiratory infection. However, the underlying mechanisms are unknown. Methods: To investigate how MSCs regulate the lung immunity and improve the defence against respiratory infection, we infected MSC‐treated wild‐type and lupus‐prone mice with Haemophilus influenzae intranasally and determined the clearance of bacteria. Tissue damage and inflammatory cytokines were measured by H&E staining and ELISA separately. Immune cell subsets in the tissues were analysed by flow cytometry. Results: MSC pretreatment prevented overwhelming inflammation and accelerated bacterial clearance in both wild‐type and lupus‐prone mice. Tregs increased dramatically in the lung after MSC treatment. Adoptive transfer of Tregs isolated from MSC‐treated mice offered similar protection, while deletion of Tregs abrogated the protective effects of MSCs. The majority of the intravenously injected MSCs were engulfed by lung phagocytes, which in turn produced CXCL9 and CXCL10 and recruited tremendous CXCR3 + Tregs into the lung. Compared with their CXCR3 − counterparts, CXCR3 + Tregs displayed enhanced proliferation and stronger inhibitory functions. Neutralisation of CXCL9 and CXCL10 significantly downregulated the migration of CXCR3 + Tregs and eliminated the benefits of MSC pretreatment. Conclusion: Here, we showed that by recruiting CXCR3 + Tregs, MSC treatment restricted the overactivation of inflammatory responses and prevented severe symptoms caused by infection. By discovering this novel property of MSCs, our study sheds light on optimising long‐term immunosuppressive regimen for autoimmune diseases and other immune disorders. Abstract : Unlike traditional immunosuppressants, which inadvertently impair a patient's antimicrobial immunity during therapy, mesenchymal stem cells (MSCs) reduce the incidence and duration of respiratory infection. MSCs are phagocytosed by lung cells and recruit CXCR3 + Tregs which could prevent overwhelming inflammation and accelerate bacterial clearance. Our study highlights the application of MSCs in treating patients who need a long‐term immunosuppressive regimen.